A Study on Success Rate of Candlesticks When Trading in Major Commodity Like Crude Oil - Bhaskar, G. (International Journal For Research In Business, Management And Accounting, 2015)
A candlestick is a type of Charts used under Technical analysis. It conveys the same information represented in bar charts, but are visually displayed differently. The Open, High, Low and Close of the chosen trading period will be represented in a single candle. Historically, candlestick charts are the oldest form of charts that have been used for predicting prices of rice. During this era in Japan, Munehisa Homma became legendary by making a fortune in the rice trade using candlestick analysis. He is said to have performed over 100 consecutive winning trades with this method.